The Female Absolute and the Relative Male. The Gender Relations According to Georg Simmel - Bianco, Adele (Simmel Studies)

(untitled) (Edizioni ETS, 2021)
This paper focuses the attention on Simmel’s selected writings on women, love and gender relations. This paper is structured as follows. The first section focuses on the image of woman presented by Simmel. Although his arguments sound “old fashioned”, he gives a positive evaluation of woman. The second section is devoted to the analysis of the gender relations that has led to woman subordination. The third section analyses Simmel's idea of male-female relationships based on the domination/subordination paradigm. The last section shows how Simmel's work devoted to this topic can drive our researches today.